LINKS BETWEEN SOCIAL NETWORK CHARACTERISTICS AND PHYSICAL ACTIVITY IN SENIOR HOUSING. (11th November 2018) - Webster, N; Alexander, N; Antonucci, T
Abstract: Only 16% of people age 65+ engage in recommended levels of physical activity, putting a vast majority of older adults at risk for poor health outcomes. Social networks effect health behaviors and may have particularly powerful effects in senior housing communities where residents live in close proximity. In this study we examine the social network characteristics (contact frequency, support, and respect) of residents in senior housing and investigate links with physical activity. Data were collected through face-to-face interviews conducted with 46 residents in an affordable (HUD subsidized) senior housing community in Southeast Michigan. Residents were on average age 73, 78% were female, 80% reported being limited in some way due to their health, and 17% reported engaging in physical activity in the past month with other residents. Those engaging in physical activity with other residents compared to those not were significantly more likely to do crafts (88% v. 42%) and attend events (e.g., concerts, lectures) (75% v. 26%). Residents who reported engaging in more moderate intensity physical activities (e.g., dancing, brisk walking) during a typical week in the past month reported significantly more respect for other residents in the community (r=.37; p<.05). Similarly, residents who reported brisk walking or walking uphill in the past month reported significantly more respect for other residents compared to those not engaging in these activities (4.2 v. 3.8; 4.4 v. 3.8). Results highlight the important role of respect among residents in facilitating physical activity, which can be incorporated into interventions tailored for senior housing communities.